Quantized Multimodal Dental X-Ray Models vs Single-Modality CNNs on Edge Devices - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: How does the performance of quantized multimodal dental X-ray models compare to single-modality CNNs in terms of mAP (mean Average Precision) on edge devices under varying input resolutions. 5 claims were extracted from source literature; 5 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.3/10. This report is a mach
Machine-generated literature synthesis.